Imprisonment, freedom, and literary opacity in the work of Nawal El Saadawi and Assia Djebar - Hiddleston, J (2010)
In her astute study of contemporary Arab women writers, Anastasia Valassopoulos begins by noting the pitfalls of much existing criticism of writers such as El Saadawi and Djebar in the West. Citing Amal Amireh's article on the fraught history of the reception of El Saadawi in Egypt and in Europe, Valassopoulos comments that Arab women's literature tends to be seen as 'documentary', and this obscures the 'core issue of representation' as it is explored and challenged by women writers. In the face of this omission, the present article explores a selection of works by El Saadawi and Djebar from an aesthetic perspective. El Saadawi and Djebar use literary writing as a means to escape the constraints placed upon them by patriarchy, as well as by colonialism, and uphold creativity and poetry as a possible release from imprisonment. This article also uses Glissant's and Bhabha's concepts of literary opacity and the right to narrate as a partial framework for a reading of the relation between writing, freedom and aesthetic form in the works of El Saadawi and Djebar. El Saadawi and Djebar purposefully deploy a form of self-effacement, both in their autobiographical representations and in their portraits of female characters, also akin to Trinh Minh-ha's strategy in Woman, Native, Other. Minh-ha's dissemination of the writing voice, and the affirmation of collective solidarity between multiple but internally fragmentary feminist positions, serves, then, as a further theoretical backdrop for El Saadawi's and Djebar's use of opacity and the right to narrate as tools in an active feminist resistance to sexist and racist discourses. Both El Saadawi and Djebar use their writing to conceive women's liberation from various forms of imprisonment, and they figure women's fractured, convoluted and at times opaque self-expression as a direct form of resistance to both patriarchal and colonial oppression. © The Author(s) 2010.